Alagebrium reduces glomerular fibrogenesis and inflammation beyond preventing RAGE activation in diabetic apolipoprotein E knockout mice - Watson, Anna M. D.; Gray, Stephen P.; Bierhaus, Angelika (Diabetes, 2012)
Advanced glycation end products (AGEs) are important mediators of diabetic nephropathy that act through the receptor for AGEs (RAGE), as well as other mechanisms, to promote renal inflammation and glomerulosclerosis. The relative contribution of RAGE-dependent and RAGE-independent signaling pathways has not been previously studied in vivo. In this study, diabetic RAGE apoE double-knockout (KO) mice with streptozotocin-induced diabetes were treated with the AGE inhibitor, alagebrium (1 mg/kg/day), or the ACE inhibitor, quinapril (30 mg/kg/day), for 20 weeks, and renal parameters were assessed. RAGE deletion attenuated mesangial expansion, glomerular matrix accumulation, and renal oxidative stress associated with 20 weeks of diabetes. By contrast, inflammation and AGE accumulation associated with diabetes was not prevented. However, treatment with alagebrium in diabetic RAGE apoE KO mice reduced renal AGE levels and further reduced glomerular matrix accumulation. In addition, even in the absence of RAGE expression, alagebrium attenuated cortical inflammation, as denoted by the reduced expression of monocyte chemoattractant protein-1, intracellular adhesion molecule-1, and the macrophage marker cluster of differentiation molecule 11b. These novel findings confirm the presence of important RAGE-independent as well as RAGE-dependent signaling pathways that may be activated in the kidney by AGEs. This has important implications for the design of optimal therapeutic strategies for the prevention of diabetic nephropathy.